Gestão participativa e política de patrimônio no Município de Belo Horizonte: realidade ou mito? - Nilo Lima de Azevedo (Universidade do Vale do Rio dos Sinos (UNISINOS), 2005)
This article analyzes the protection of buildings considered as cultural patrimony in the city of Belo Horizonte, state of Minas Gerais, on the basis of the actions undertaken by the Deliberative Council for Cultural Patrimony of the Municipality of Belo Horizonte. It particularly tries to assess whether the Council was able to establish a decentralization process and a broad grassroots participation in the implementation of the municipal public policy in this area by bringing to the political discussion arena representative organizations of the various takeholders.